Case Report: A patient with cardiac rhabdomyoma associated with embryonal developmental dysplasia of neuroepithelial tumors, presenting with recurrent cyanosis of the face and lips - Liu, Qian; Long, Yuan (Frontiers in Pediatrics, 2025)
BackgroundCardiac rhabdomyoma is a benign cardiac tumor predominantly found in children and is often associated with tuberous sclerosis. Typically, this tumor is asymptomatic; however, its size and location can compromise cardiac function, potentially leading to heart failure, which may manifest as cyanosis of the lips and respiratory difficulties. Embryonal dysplastic neuroepithelial tumor is a slow-growing benign brain tumor classified as a neuroepithelial tissue tumor. It typically does not undergo malignant transformation and originates from the cerebral cortex. The concurrent occurrence of cardiac rhabdomyoma and embryonal dysplastic neuroepithelial tumor, manifesting as facial and perioral cyanosis, is relatively uncommon in pediatric patients.Case reportWe present a case of a 4-year-and-4-month-old boy who was admitted for “recurrent facial and perioral cyanosis over the past year”. Prenatal four-dimensional ultrasound revealed strong echogenic foci within the ventricles, suggesting the presence of a cardiac rhabdomyoma. One year prior to admission, the child experienced recurrent episodes of facial and perioral cyanosis. Considering his medical history, the admission diagnosis was left ventricular outflow tract obstruction due to the cardiac rhabdomyoma. However, following a systematic evaluation and investigation, the definitive cause of the “facial and perioral cyanosis” was determined to be an embryonal dysplastic neuroepithelial tumor. The child subsequently underwent tumor resection, and pathological examination confirmed the preoperative diagnosis. Postoperatively, the child has remained free of facial and perioral cyanosis for over two years.ConclusionThe concurrent occurrence of cardiac rhabdomyoma and embryonal dysplastic neuroepithelial tumor is exceedingly rare. Clinicians must exercise caution when evaluating the etiology of a child's symptoms. This case emphasizes the necessity of increasing clinicians’ awareness of this rare concomitant occurrence and highlights the vital role of timely diagnosis and surgical intervention in enhancing patient outcomes.